Variabilidade fluviométrica do Rio Tapajós em Santarém - PA - AMORIM, Letícia Lorena Braga (2019)
Was studied the diagnosis on the climatology and variability fluviometric (quota or level) of the Tapajós River in the city of Santarem in Para state, where we used data from years 1969 to 2009 of the Agencia Nacional de Aguas. We analyzed the long-wave radiation (OLR), precipitation, sea surface temperature (SST) of the Pacific Ocean and the Atlantic to the quarters in October, November and December (OND), January, February and March (JFM), April, May and June (AMJ) and July, August and September (JAS). It was made the climatology of precipitation and elevation data, the data were selected from these extreme years, with positive and negative anomalies. The quarter with the highest share was in April, May and June, and lowest level was in October November December. Largest share of the Tapajós River was registered in 2009 in the month of May, with 819 cm and the lowest was in 1995 with 5 cm in the month of October. The higher altitudes are associated with La Niña, negative temperatures on the surface of the Pacific Ocean and with most of the Atlantic Ocean SST with negative, negative values of outgoing longwave radiation and increased precipitation. The lower elevations are associated with El Niño, or positive temperature on the surface of the Pacific Ocean, Atlantic Ocean dipole with positive, positive values of outgoing longwave radiation and lower rainfall.